The Effect of Moringa Leaf Administration on Hb Levels in 3rd Semester Pregnant Women - Roslina Roslina; Nila Widya Keswara (PPNI UNIMMAN, 2026)
Anemia during pregnancy is a major public health issue, especially in developing countries like Indonesia, contributing to maternal morbidity and adverse pregnancy outcomes. The second trimester, marked by increased iron needs due to plasma volume expansion and fetal growth, is critical for preventing anemia. Moringa leaves (Moringa oleifera), rich in micronutrients, may serve as an effective nutritional intervention to enhance hemoglobin levels in pregnant women. This study aimed to assess the impact of moringa leaf supplementation on hemoglobin levels in second-trimester pregnant women. Using a one-group pretest-posttest quasi-experimental design, the study was conducted at the Tadoy Community Health Center in Bolaang Mongondow Regency from October to November 2025, involving 25 pregnant women selected via purposive sampling. Hemoglobin levels were measured before and after the supplementation. Data analysis, including the Shapiro-Wilk test and Wilcoxon Signed Rank Test, indicated significant changes in hemoglobin levels (p = 0.000). The results showed a notable increase in hemoglobin levels post-supplementation, supporting the potential of moringa leaves as a safe, affordable, and effective intervention. This finding suggests that moringa leaves could be integrated into antenatal care and nutrition education to help prevent anemia in pregnant women.